The Analysis of Code Mixing of English Department Students of Universitas Bandar Lampung - Yanuarius Yanu Dharmawan; Yanuar Dwi Prastyo; Maulinda Maulinda; Nurdiawansyah Nurdiawansyah (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2020)
Sociolinguistics is the study about language in a society. In learning about the language in society, there is a phenomenon called code mixing. In this study we focus on the reason of doing code mixing. It is to find the reasons of code mixing occur at English Department Universitas Bandar Lampung. This study uses qualitative research design aiming to analyze the reason of using code mixing. The results were gained from observation and interview. Observation is aimed to find out the words uttered to be classified into reasons. The interview goal is to get more information from the students. The result shows that some respondents tend to mix the language because they feel comfortable in doing this. They cannot express some words in Indonesian. To sum up, the code mixing occurs unintentionally and spontaneously